COMPETITIVENESS OF HIGHER EDUCATION SYSTEM: INTERNATIONAL DIMENSION - Anna Verbytska; Nataliia Kholiavko (Izdevnieciba "Baltija Publishing", 2020)
The globalization of the scientific-educational area determines the search for new competitive advantages of universities. One of the modern instruments of competition in the world educational services market is universities ranking. Nowadays the educational rankings are widespread; they are studied by researchers and experts of international organizations. In the same time the high dynamism of scientificeducational area requires the permanent monitoring of the competitive positions of the national higher education systems. The purpose of the article is to analyze the competitive positions of higher education systems of selected countries in the world rankings, as well as to identify the directions of increasing their competitiveness in the context of globalization and digitization of the scientific-educational area. The authors studied the methodology of a range of popular rankings of educational systems, and analyzed the ranks of selected countries (United States of America, Switzerland, United Kingdom, Sweden, Denmark, Canada, Finland, Norway, Ukraine, Germany, France, Austria, Poland, China, and Spain). The selection is based on the differentiation of the countries according to the geographic position and ranking position. The source of data: bases of international organizations OECD, World Bank, UNESCO, ILO; and rankings ARWU, SCImago, Webometrics, and Leiden Ranking. Based on the comparative analysis, the article concludes that the increasing of competitiveness of the national higher education system needs the use of integrated approach combining the set of educational, research, financial, internationalization, and managerial components. The authors emphasized the urgency of developing and implementing institutional strategies for internationalization of universities, synchronized with national ones.